ANALISA DAMPAK KEMISKINAN AKIBAT FAKTOR KONSUMSI, TRANSPORTASI, DAN HUNIAN - Imalinda Deryane (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
Economic problems are problems that arise in everyday life such as unemployment, poverty, inflation, debt, and others. Riau Island which has more water has effectively made water transportation as an appropriate accessibility role to ensure the accessibility of people between regions to meet their needs. However, the absence of transportation facilities makes it difficult for people in disadvantaged areas to meet their needs. Economically, the basic needs that are not far away are the needs for food, clothing and shelter. The need for shelter becomes a secondary need if the needs for clothing and food are not met. One of the obstacles due to the lack of transportation facilities is education. Education itself has an important role in the social and economic welfare of the community. Transportation can also hamper the small businesses of coastal island communities, due to the difficulty of accessing markets. From consumption issues, local governments need to pay attention to the economic aspects of the community, namely creating jobs, attracting investors in tourism, industry, and others to create jobs in order to continue to exist